ENHANCING LEADERSHIP AND MANAGEMENT SKILLS THROUGH BLUE LIGHT MURAQABA MEDITATION (BLMM) - Suleman Sukander; Iram Shahzadi; Dr. Ismat Bano (International Journal of Contemporary Issues in Social Sciences, 2024)
This study investigates the potential benefits of Blue Light Muraqaba Meditation (BLMM) on leadership and management abilities. Blue light visualization meditation (BLMM) is one type of meditation that is intended to improve mental acuity, tranquility, and sharpness. The study investigates the ways in which BLMM can improve decision-making, emotional intelligence, and strategic thinking, among other managerial and leadership abilities. The study uses a mixed-methods approach to record in-depth perspectives through qualitative interviews and quantitative leadership skills assessments conducted both before and after the BLMM intervention. The results show that BLMM greatly improves a number of leadership and management-related areas, providing a new, comprehensive instrument for professional progression.